Teratogenic Effects of Ethanolic Cinnamomum burmanni Leaf Extract on Fetal Development in White Mice (Mus musculus L.) - Zeynab Noroozi; Jose Dale Viacrucis Iii (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study aims to evaluate the teratogenic effects of ethanolic extract of Cinnamomum burmanni leaves on fetal development in white mice (Mus musculus L.). Methodology: This research is a laboratory experimental study using a Completely Randomized Design (CRD) and a pretest-posttest control group design. A total of 24 pregnant female mice were divided into four treatment groups: negative control (Na CMC), P1 (250 mg/kgBW), P2 (500 mg/kgBW), and P3 (1000 mg/kgBW). The extract was administered orally during the organogenesis period. Observed parameters included fetal weight and length, morphological abnormalities, hemorrhage, ossification, and resorption sites. Data were analyzed using One-Way ANOVA followed by Duncan’s test. Main Findings: The results of the study showed that administration of ethanolic extract of Cinnamomum burmanni leaves significantly (p < 0.05) reduced fetal weight and length, and induced morphological abnormalities and hemorrhage at doses of 250 mg/kgBW and above. However, no abnormalities were observed in the ossification process or resorption sites. Novelty/Originality of this study: The ethanolic extract of Cinnamomum burmanni leaves demonstrated potential teratogenic effects on fetal development in white mice, characterized by growth retardation and morphological abnormalities. This study provides an important basis for evaluating the safety of using this plant during pregnancy.